2015
DOI: 10.4236/ojepi.2015.51004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of <i>Leptospira</i> in Rats, Water and Soil in Bantul District Yogyakarta Indonesia

Abstract: Leptospirosis is a potential threat to public health. An increasing number of people infected with Leptospira were reported in Bantul District, Yogyakarta special region with a case fatality rate (CFR) of 7.8%. Infected areas in the district have increased from 2 to 15 sub districts. Leptospirosis is caused by Leptospira bacteria and spread by direct contact with infected rodents and indirect contact through contaminated water or soil. Leptospira in rats, water and soil were detected using real-time quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
0
21
0
6
Order By: Relevance
“…DNA samples obtained from kidney tissue of rats. Leptospira detection by using qPCR was showed positive in 25 samples [21]. However, only 6 samples were confirmed as pathogenic Leptospira by using standard PCR (Figure 1).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…DNA samples obtained from kidney tissue of rats. Leptospira detection by using qPCR was showed positive in 25 samples [21]. However, only 6 samples were confirmed as pathogenic Leptospira by using standard PCR (Figure 1).…”
Section: Resultsmentioning
confidence: 85%
“…However, rats are the most prominent reservoir among others. Rats are the most potential vector and reservoir for Leptospira transmission to human being [21]. Furthermore, Barcellos et al reported that the distribution of leptospirosis in human were concentrated in areas where rats were highly populated, as well as areas with unfavorable trash management and poor sanitary conditions [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in general occurs through direct contact with infected animals such as the bites of animal like rodent and the open wounds which are exposed to urine or body fluids from infected animals. The disease can also be transmitted through direct contact with the water environment and soil contaminated with the Leptospira bacteria (Chua 2010;Sumanta, 2015). The diagnosis of leptospirosis is done through confirmation of laboratory results to determine the cause of the infection in the suspected source of infection and the reservoir containing leptospirosis bacteria (Chua, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial analysis is an analysis of the territorial aims to determine the association of an event toward the aspects of space. Spatial analysis area can be used to determine the deployment, to cluster and to predict the occurrence of leptospirosis in the region, as well as to evaluate risk factors for leptospirosis disease which is associated with environmental and social aspects (Sumanta, 2015;Soares, 2010).…”
Section: Introductionmentioning
confidence: 99%